Effects of life history strategy on the diversity and composition of the coral holobiont communities of Sabah, Malaysia - Golam Rabbani; Lutfi Afiq-Rosli; Lee, Jen Nie; Zarinah Waheed; Benjamin J. Wainwright (NLM (Medline), 2025)
Coral-associated microbes have essential roles in promoting and regulating host function and health. As climate change advances and other environmental perturbations increasingly impact corals, it is becoming ever more important that we understand the composition of the microbial communities hosted. Without this baseline it is impossible to assess the magnitude and direction of any future changes in microbial community structure. Here, we characterised both the bacterial and Symbiodiniaceae communities in four coral species (Diploastrea heliopora, Porites lutea, Pachyseris speciosa, and Pocillopora acuta) collected from Sabah, Malaysia. Our findings reveal distinct microbial communities associated with different coral species tending to reflect the varied life history strategies of their hosts. Microbial communities could be differentiated by collection site, with shifts in Symbiodiniaceae communities towards more stress tolerant types seen in samples collected on the shallow Sunda Shelf. Additionally, we identified a core microbiome within species and a more discrete core between all species. We show bacterial and Symbiodiniaceae communities are structured by host species and appear to be influenced by host life history characteristics. Furthermore, we identified a core microbiome for each species finding that several amplicon sequence variants were shared between hosts, this suggests a key role in coral health regardless of species identity. Given the paucity of work performed in megadiverse regions such as the Coral Triangle, this research takes on increased importance in our efforts to understand how the coral holobiont functions and how it could be altered as climate change advances.